C-Simultaneous Localization and Mapping (C-SLAM) for Underwater Robotics Using Sonar Data - Gu, Zhaowen (Transactions on Computer Science and Intelligent Systems Research, 2024)
Since the current methods for precise underwater navigation are either insufficient in terms of accuracy or environmentally unfriendly, C-SLAM aims to address the critical issue of underwater localization for Uncrewed Underwater Vehicles (UUVs) undertaking seabed surveys. To improve the accuracy of navigation and overall operational efficiency, we’ll use Simultaneous Localization and Mapping (SLAM) techniques, which can achieve precise localization by looking at matching landmarks and Inertial Navigation System (INS) measurements from sonar data. While processing these sonar data, C-SLAM will adjust position estimation errors through loop corrections and pose-graph optimization methods. As a result, it can generate a detailed 2D/3D visual representation of the vehicle’s trajectory in the seafloor environment. Considering the importance of exploring the seafloor for scientific research, resource identification, and environmental monitoring, it is essential to track the accurate trajectory of UUVs, and our final deliverable, C-SLAM, is dedicated to tackle this issue.